Tanggung Jawab Hukum Internasional atas Kejahatan Kemanusiaan di Gaza - Nada, Nihalun; el-Afaf, Ishmah (Laboratorium Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya (https://uinsa.ac.id/fsh/facility), 2024)
Abstract: Law enforcement against the crime of genocide and crimes against humanity in Gaza is a major concern in international law. This article analyzes international legal responsibility for crimes committed in the Israeli-Palestinian conflict, focusing on the jurisdiction of the International Criminal Court (ICC) and the role of international organizations in holding perpetrators accountable. This research uses a normative juridical method with a literature research approach, examining various international legal instruments such as the Rome Statute, the Geneva Convention, and United Nations (UN) resolutions. The results show that although Palestine has been a member of the ICC since 2015 and has the right to file demands, law enforcement against Israel faces jurisdictional constraints, the principle of state sovereignty, as well as international geopolitical dynamics. In addition, there are obstacles in the implementation of international humanitarian law due to the lack of cooperation between Israel and international judicial bodies. This article emphasizes the importance of global commitment to upholding justice for victims, as well as the need to reform international law enforcement mechanisms to be more effective in dealing with cases of genocide and crimes against humanity.Keywords: International Law, Genicide, Crimes Against Humanity, Gaza, ICC. Abstrak: Penegakan hukum terhadap kejahatan genosida dan kejahatan terhadap kemanusiaan di Gaza menjadi perhatian utama dalam hukum internasional. Artikel ini menganalisis tanggung jawab hukum internasional atas kejahatan yang terjadi dalam konflik Israel-Palestina, dengan fokus pada yurisdiksi Mahkamah Pidana Internasional (International Criminal Court/ICC) dan peran organisasi internasional dalam menuntut akuntabilitas pelaku. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan penelitian kepustakaan, mengkaji berbagai instrumen hukum internasional seperti Statuta Roma, Konvensi Jenewa, serta resolusi Perserikatan Bangsa-Bangsa (PBB). Hasil penelitian menunjukkan bahwa meskipun Palestina telah menjadi anggota ICC sejak 2015 dan memiliki hak untuk mengajukan tuntutan, penegakan hukum terhadap Israel menghadapi kendala yurisdiksi, prinsip kedaulatan negara, serta dinamika geopolitik internasional. Selain itu, terdapat hambatan dalam implementasi hukum humaniter internasional akibat minimnya kerja sama Israel dengan badan peradilan internasional. Artikel ini menegaskan pentingnya komitmen global dalam menegakkan keadilan bagi korban, serta perlunya reformasi mekanisme penegakan hukum internasional agar lebih efektif dalam menangani kasus kejahatan genosida dan kejahatan terhadap kemanusiaan.Kata Kunci: Hukum Internasional, Genosida, Kejahatan Kemanusiaan, Gaza, ICC.